Corporate strategy for Cavite Packaging Corporation - Cocabo, Emilia (Animo Repository, 1999)
Packaging is defined as the totality of products, services and systems used to prepare goods for prevention, transport, distribution, storage, retailing and consumption. Under which there are different packaging materials namely: plastic, woods, glass, metal, textile and boxes. The corrugating box industry refers to the industry manufacturing corrugated boards, boxes and related products. In the Philippines, there are about 45 manufacturers categorized as corrugators. Main raw materials consist of Kraft liner board and corrugating medium. About 40 percent of paper are imported and 60 percent are produced locally. There are many suppliers of paper based packaging products in the Philippines as well as abroad so the industry has plenty of choices when it comes to choosing the sizes, kinds and quality of paper that they need. Using Michael Porters five forces analysis the industry is analyzed, conclusions as well as abroad so the industry has plenty of choices when it comes to choosing the sizes, kinds and quality of paper that they need. Using Michael Porters five forces analysis the industry is analyzed, conclusion derived are there is low threat of new entrant because of high capital requirements, high access to distribution channel, high economies of scale, moderate threats of substitutes since it is possible that customers would want to switch to another packaging material, high threats of existing competitors since competitors are also capable of producing the same product, have same available resources, machine are also capable of producing the same product, have same available resources, machine capacity, high threats of buyers since there are several competitor buyer have the edge, low threats of suppliers due to several existing suppliers. Cavite Packaging Corporation (CPC) is engaged in the manufacturing of corrugated boxes and provides packaging services to different manufacturing industries such as Food and beverage, textiles and garments, paints, pharmaceuticals, paper, printing and publishing, cigarettes and other tobacco products and electronics. Cavite Packaging Corporations was established in 1996. The Corporation is owned by the The Cocabo Family headed by its Chairman Mr. Teresco Cocabo, who has more than 40 years experience in the corrugated box industry company operation, being the owner of another similar established corrugated box plant together with some other relatives. The family saw the need to established a better and bigger plant to meet the increasing and changing demands of its existing customers as well as its prospective customers to stay competitive, this was one of the major driving why Cavite Packaging Corporation was conceptualized and established.